DIFFERENT APPROACHES TO THE DEFINITION OF CONTENT AND STRUCTURES OF RESPONSIBILITY - R.V. Kondratenko (Academy of Cognitive and Natural Sciences, 2022)
The author of the article highlights the different approaches disdinguishing the structural components of responsibility.